2018 Interim Surveillance Review. (Policy Papers; Policy Paper, 2018)
Fund surveillance has become better adapted to the global conjuncture, and more integrated and risk-based. The recommendations of the 2014 Triennial Surveillance Review (TSR) focused on helping members navigate the post crisis challenges. Bilateral and multilateral surveillance discussions are underpinned by a shared and deeper understanding of global interconnectedness and linkages across sectors. There has also been progress in core areas such as risk work, fiscal and external sector analysis, and in integration of macrofinancial analysis and of macrostructural policy work that aims to reinvigorate productivity and growth, and promote inclusiveness. The ongoing efforts to align surveillance inputs with risks is also enhancing the Fund's ability to support members more effectively. Continuing efforts along several dimensions will be needed to further advance surveillance ahead of the 2019 Comprehensive Surveillance Review (CSR). These include planned refinements to external sector assessments, sustaining progress on macrofinancial surveillance, addressing data gaps, and incorporating lessons from pilot efforts including on macrofinancial, macrostructural and emerging issues. Efforts to meet surveillance challenges in low income countries also will continue. Outward spillover work, particularly from the largest economies, should receive greater prominence in Article IV reports. Further work is also needed to make policy advice more persuasive by better leveraging cross-country policy experiences and integrating technical assistance. Lessons from implementing the TSR recommendations should help ensure further progress. A major investment has been made to deepen the analysis that supports surveillance. With a dramatic increase in the range of analytical approaches and tools available, selectivity and tailoring are ever more crucial. The Fund's internal processes have proven flexible enough to deliver on key areas, but will require continual adaptation to keep pace with evolving challenges. Strategies for human resources, capacity development, knowledge management, and data and statistics should further reinforce surveillance priorities. Looking ahead, the 2019 CSR will further anchor the Fund's surveillance in a world of rapid technological change. The increased pace of technological progress could have far-reaching implications for the global economy, finance, and policy making, possibly fundamentally altering the surveillance landscape. Coupled with rising inequality and possible adoption of inward-looking policies, the impact on the membership could be profound. Engagement with members, stakeholders, and experts will be central in determining how the 2019 CSR will address these challenges.